The distribution of MEFV mutations in Turkish FMF patients: multicenter study representing results of Anatolia - DİRESKENELİ, RAFİ HANER (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2019)
Background/aim: The distribution of Mediterranean fever (MEFV) gene mutations in Turkish familial Mediterranean fever (FMF) patients varies according to geographic area of Turkey. There is a need for highly representative data for Turkish FMF patients. The aim of our study was to investigate the distribution of the common MEFV mutations in Turkish FMF patients in a nationwide, multicenter study. Materials and methods: Data of the 2246 FMF patients, from 15 adult rheumatology clinics located in different parts of the country, were evaluated retrospectively. The following mutations have been tested in all patients: M694V, M680I, M694I, V726A, and E148Q. Results: There were 1719 FMF patients with available genetic testing. According to the genotyping, homozygous M694V, present in 413 patients (24%), was the most common mutation . One hundred and fifty-four (9%) of patients had no detectable mutations. Allele frequencies of common mutations were: M694V (n = 1529, 44.5%), M680I (n = 423, 12.3%), V726A (n = 315, 9.2%), E148Q (n = 214, 1%), and M694I (n = 12, <1%). Conclusion: In this large-scale multicenter study, we provided information about the frequencies of common MEFV gene mutations obtained from adult Turkish IMF patients. Nearly half of the patients were carrying at least one M694V mutations in their alleles.
Keywords: Familial Mediterranean fever; Mediterranean fever gene mutations; M694V; Turkey; FAMILIAL MEDITERRANEAN FEVER; GENE-MUTATIONS; FREQUENCY; REGION; TURKEY; DIAGNOSIS; GENOTYPES; SPECTRUM; PROVINCE; DISEASE